Estudio estratigráfico con fines de cimentación en el distrito de Morales - Sánchez Chávez, Elmer Rafael (1998)
In Chapter 1 (GENERAL}, give the reader information about the location, climate, vegetation, relief and altitudes of the Morales district; Likewise, for to locate them different terraces is made the rising topographic to curves to level that us served in the zoning of the soils. In chapter II (WORK CARRIED OUT}, is exposed all work performed such as: topography, geology, soil mechanics and the processing of the information.) To be able to zone the area, we rely on the plane curves to level and by each registered calicata visited the excavations that were made at that time, such as: excavations for the foundations of houses, trenches for drain pipes and other adjacent excavations. The same was delimited areas which would represent each calicata. In chapter III (GEOLOGY). explain the theories of greater today and whose Foundation are the more accepted in the medium; as are the theory of ' ~ ectonica of P...